Experience with various reconstructive techniques for meningomyelocele defect closure in India. (September 2019) - Sharma, Mukesh Kumar; Kumar, Naveen; Jha, Manoj K; N, Umesh; Srivastava, R.K.; Bhattacharya, Sameek
Abstract: Background: The estimated incidence of spina bifida is 1–2 cases per 1000 population. In earlier literature, the global prevalence of meningomyelocele (MMC) is reported as 0.8–1.0 per 1000 live births. This retrospective study analyses the outcome of various surgical procedures performed for the closure of MMC defects. Method: A total of 22 patients with MMC defects who underwent repair at our institute from July 2016 to August 2018 were included in the study. A retrospective review of all the cases operated was completed to analyse patient demography including defect size, defect location, surgical procedures, complications and the final outcome. Results: Out of 22 cases, wherein the neurosurgery department sought help from the plastic surgery department, 11 defects were closed using the Limberg flap technique, 4 defects were closed with either primary closure or the double flap rotation flaps, one defect was closed using the triple rotation flap and 2 defects were closed using the local transposition flap cover technique. Complications were noted in only three cases. One patient had a local wound infection, while in two other cases, wound dehiscence was observed. All 3 cases were managed conservatively. On average, it takes approximately 70 days in India to close such defects. Conclusion: MMC defects can be effectively managed with local flap options such as Limberg flap, local transposition flap or rotation flaps. Various reasons for the delay in closure were reported in patients late to our centre, when the first point of contact was with other departments.